A resistência da literatura: leitura e escrita literária enquanto arte de fazer - Vieira, Aline Silva (2024)
Reading (especially literary reading), considered as a complex process of creating meaning through the interaction of author-text-reader, is understood in this dissertation as a practice of resistance, as its execution leads to the creation of a personal space that allows for the establishment of both individual and collective identity. Drawing from Michel de Certeau's conception of society (2013, 2014), where humans are situated within a consumer society, where control primarily occurs through the circulation of goods, assumption of roles, and social codes, power relations occur among these systems. According to the author, there are strategic practices - those that evoke a specific place - and tactical practices - those that do not have a specific place, inscribing themselves in the place of others. In this investigation, we aim to insert literary reading as a tactical action, as the reader can and has the potential to create within the space of others; and the writing of literature as an action with tactical characteristics. Based on the reflections of the aforementioned author, as well as the ideas of Roger Chartier (1998, 1999, 2011a, 2011b), Michel Foucault (2001, 2023), Alfredo Bosi (2002), Wolfgang Iser (1979, 1996), Roland Barthes (2004, 2013), Umberto Eco (2019), Paul Zumthor (2018), Michèle Petit (2013), and Antonio Candido (2004), who reflect on the issues of literary reading and writing, interpretation, and their relationships with society and otherness, this dissertation seeks to understand how literary reading and writing play a decisive role in resisting systems of power, positioning the figures of reader and literary author as protagonists of this silent movement we call resistance. By understanding how literary reading allows for the creation of a refuge, fostering the construction of self-awareness and awareness of others, and literary writing as a subversion of language power, this work inserts itself into a field of reflection on literary reading and writing as actions of constructing meaning, forming identities, and promoting resistance against the impositions of power structures, whether they be economic, cultural, social, or otherwise.